The Development of Learning Activities in Pronunciation Practice Class through Lesson Study - Magfirah Thayyib; Ramdani Syam (Ethical Lingua: Journal of Language Teaching and Literature, 2015)
This study aims at describing the development of learning activities in pronunciation practice class through lesson study. The number of sample is two passive students (student A and B) obtained by using purposive sampling. The instruments of this research are observation sheet and documentation. The data are analyzed quantitatively. The result of this research shows the learning activities development of student A and B has fluctuated. The learning activities of student A has increased from 2.25 to 2.7 in the second cycle, both in fairly active category. It becomes 2.55 in the third cycle and 2.25 in the fourth cycle. While the learning activities of student B has increased from 2.35 with fairly active category to 3.05 with active category in the second cycle. In the third cycle it becomes 2.65 and in the fourth cycle it becomes 2.5. It means lesson study can improve the learning activity of passive students to be fairly active or active.